THE ROLE OF PRIVATE BANKS IN INCREASING TAX REVENUESAPPLICATION CASES IN THE GENERAL TAX AUTHORITY (World Economics and Finance Bulletin, 2024)
This study aims to explain the role of private banks in increasing tax revenues, by reviewing applied cases in the General Authority for Taxes / Mahmoudiyah Branch, showing the role of bank transfers sent from those banks in enhancing the increase in tax revenues. The researchers concluded that, through the information that private banks possess When dealing with taxpayers, the tax administration can access the taxpayer’s real income and uncover the tax evasion process of some taxpayers, which helps expand the tax base and increase tax revenues. The researchers recommend that in order to facilitate the exchange and access of information between the tax administration and private banks, we must emphasize the necessity of strengthening cooperation and coordination between them in order to overcome the difficulties and problems that may hinder or delay this by finding ways of communication and understanding that are more rapid and effective.